Designing play for dark times. (June 2017) - Yamada-Rice, Dylan
This article reports on a knowledge-exchange network project that had the core aim of informing the development of a video game for hospitalized children. In order to do this, it brought together hospital play specialists, academics and representatives from the digital games industry to co-produce knowledge that could be used in the future production of such a product. The project came about in relation to having identified a lack of research about and actual physical-digital games designed specifically for children living in adverse ('dark') times. This is despite the fact that there is a substantial body of research that has shown how play is beneficial for helping children make sense of what is happening to them, and thus results in better mental, emotional and physical well-being. The article describes a selection of the knowledge-exchange presentations and activities that were used throughout the project. Specifically, these activities used art-and-design-based methods as a means of knowing through making. The methods are discussed in relation to how they generated knowledge that responded to the objectives of the project. These were, firstly, to allow children to express emotions about their illness and/or being in hospital; secondly, to offer information on the hospital experience; and, finally, to develop a design that could cross physical and digital platforms with a space for open-ended child-directed play. As the overarching intention of the project was to generate knowledge across the stakeholders, the project ended by materializing the core findings from the project into a paper prototype of a game on which a hypothetical digital-physical version could be based.